2019
DOI: 10.1109/access.2019.2948704
|View full text |Cite
|
Sign up to set email alerts
|

A Task Scheduling Algorithm With Improved Makespan Based on Prediction of Tasks Computation Time algorithm for Cloud Computing

Abstract: Cloud computing is extensively used in a variety of applications and domains, however task and resource scheduling remains an area that requires improvement. Put simply, in a heterogeneous computing system, task scheduling algorithms, which allow the transfer of incoming tasks to machines, are needed to satisfy high performance data mapping requirements. The appropriate mapping between resources and tasks reduces makespan and maximises resource utilisation. In this contribution, we present a novel scheduling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Briefly, the task scheduling algorithm targets prioritizing tasks based on a defined criterion to reach higher resources’ utilization for the defined tasks in the appropriate time scheduling. The task scheduling algorithm allocates the tasks in a first-come-first-served strategy which has no criteria for assignment other than the available resources ( Al-Maytami et al, 2021 ). On the other hand, the round-robin algorithm allocates tasks following the equal processor time distribution for the participating tasks using a time unit called “quantum”.…”
Section: Real Case Study Applied In E-learning System and Experimental Resultsmentioning
confidence: 99%
“…Briefly, the task scheduling algorithm targets prioritizing tasks based on a defined criterion to reach higher resources’ utilization for the defined tasks in the appropriate time scheduling. The task scheduling algorithm allocates the tasks in a first-come-first-served strategy which has no criteria for assignment other than the available resources ( Al-Maytami et al, 2021 ). On the other hand, the round-robin algorithm allocates tasks following the equal processor time distribution for the participating tasks using a time unit called “quantum”.…”
Section: Real Case Study Applied In E-learning System and Experimental Resultsmentioning
confidence: 99%
“…Alabbadi and Abulkhair [34] proposed a novel Multi‐Objective Particle Swarm Optimisation (MOPSO) algorithm for multi‐objective task scheduling on cloud data centres, and the results showed that MOPSO can find the optimal solution and outperform other existing single and multi‐objective scheduling algorithms. Generally, previous studies only focussed on makespan [35, 36] and power usage [37, 38] in the scheduling process, or only considered the load balancing [39, 40], and employed certain algorithms to achieve multi‐objective [41, 42] or single‐objective optimisation. However, these research studies did not consider these objectives simultaneously.…”
Section: Related Workmentioning
confidence: 99%
“…Maytami et al [30], the primary goal of this study is to increase the efficiency of task scheduling while at the same time lowering computational costs. The fundamental goal is to forecast the desirable algorithm for incoming/available requests as and when necessary.…”
Section: General Load Balancing Techniquesmentioning
confidence: 99%